2005
DOI: 10.1007/s11373-005-9000-7
|View full text |Cite
|
Sign up to set email alerts
|

Activation of muscarinic K+ channels by arecaidine propargyl ester in isolated guinea-pig atrial myocytes

Abstract: Arecaidine propargyl ester (APE) was developed as a potential candidate compound for the treatment of Alzheimer's disease. APE has been shown to have cardiovascular effects. APE produces negative chronotropic and inotropic effects in isolated atria. However, the ionic mechanisms underlying the cardiovascular effects of APE in guinea-pig atria are unclear. The aims of this study were: (1) to examine the shortening effect of APE on action potential duration (APD) and to compare the difference in potency between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The activity of fibroblast or prostatic IK Ca channels has been reported to be potentially important in cell growth through a delicate control of Ca 2 þ entry (Peña andRane, 1999, Lai et al, 2007;Lallet-Daher et al, 2009;Ohya et al, 2011). A number of studies have revealed that ARE could stimulate the production of connective-tissue growth factor in buccal fibroblasts and influence the functions of neutrophils, lymphocytes or macrophages (Hung et al, 2000;Lai et al, 2007;Shen et al, 2007;Deng et al, 2009;Chen andChang, 2012, Hwang et al, 2013;Grossinger et al, 2014;Xu et al, 2014). Therefore, to what extent ARE-induced block of IK Ca channels observed in the present study is capable of exerting its adverse effects on the activity of oral keratinocytes remains to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activity of fibroblast or prostatic IK Ca channels has been reported to be potentially important in cell growth through a delicate control of Ca 2 þ entry (Peña andRane, 1999, Lai et al, 2007;Lallet-Daher et al, 2009;Ohya et al, 2011). A number of studies have revealed that ARE could stimulate the production of connective-tissue growth factor in buccal fibroblasts and influence the functions of neutrophils, lymphocytes or macrophages (Hung et al, 2000;Lai et al, 2007;Shen et al, 2007;Deng et al, 2009;Chen andChang, 2012, Hwang et al, 2013;Grossinger et al, 2014;Xu et al, 2014). Therefore, to what extent ARE-induced block of IK Ca channels observed in the present study is capable of exerting its adverse effects on the activity of oral keratinocytes remains to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Reports showed that glioma cells possess M2 muscarinic receptors, activation by acetylcholine could stimulate small-conductance Ca 2þ -activated K þ (SK Ca ) channels in neocortical pyramidal neurons (Brombas et al, 2014;Ferretti et al, 2012Ferretti et al, , 2013. ARE has been shown to suppress ether-à-gogo-related K þ current and stimulate muscarinic-K þ channels or ATPsensitive K þ channels (Chen, 2005;Yoshizumi et al, 2008;Ling et al, 2012;Zhao et al, 2012). However, whether this compound directly interacts with ion channels to perturb ion currents and change membrane potential remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…However, APE has been shown to produce negative chronotropic and ionotropic effects in isolated atria [29]. In this communication, Chen [30] showed that APE activated muscarinic K + channels and increased potassium conductance in guinea-pig atrial myocytes. In addition, APE also shortened action potential duration in the same system.…”
Section: Thaliporphine and Post-ischemia Reperfusion Injurymentioning
confidence: 85%